Maner: Managed Information Dispersal Plan for GPRS IoT Enabled Wildlife Monitoring System - Anju, V; Deeksha, A S; Deepika, B U; Lochana, K; Anusha, K L (International Journal of Computer Sciences and Engineering, 2025)
In today’s world, wildlife is an important factor in maintaining natural balance of any nation’s environment. One of the important and vital roles is played by the forest department. There are many concerns regarding the safety of wildlife, so for their security is of main concern for this purpose instrument may be mounted on them to view the present location. Bio-sensor systems comprise various types of small physiological sensors, transmission modules and processing capabilities. Hence, sensor networks can collect, transmit, and store vast volumes of environmental data, which may be used in research or monitoring wildlife.GPS used to log the longitude and latitude so that direction can be known easily. These devices are being added to them will explore the possibility of embedding GPS devices so forest department official can track their animal’s movements in real time.So by using these equipment’s we are trying to implement the basic life- guarding system for wild life in low cost and high reliability.